11. Children on their Own: Cold War Childhood Memories of Unsupervised Times - Nadine Bernhard; Kathleen Falkenberg ((An)Archive: Childhood, Memory, and the Cold War, 2024)
Childhood in formerly socialist countries is often depicted in research as ‘organised’ or ‘uniform’―a perspective we challenge in this paper. Using collective-memory work, we analyse our own childhood memories from the late GDR and memories taken from the memory archive of the Reconnect/Recollect project, focusing on unsupervised times, when institutional access to child supervision was no longer available and adult supervision could not (yet) be guaranteed. With this focus, we broaden existing literature on post/socialist childhood, which mainly focuses on institutionalized settings. Our analysis finds three patterns of unsupervised times present across different memory stories―unsupervised times perceived as freedom and contentment, responsibility, and loneliness. These patterns show that unsupervised times created opportunities for important children’s experiences to take place―from being creative to imitating adults, breaking rules, and building communities with peers and siblings. Additionally, we find many similarities across geopolitical boundaries that break down the stereotypical dichotomies of childhoods between the ‘East’ and the ‘West’.